Target-fueled DNA walker for highly selective miRNA detection. Issue 12 (25th September 2015) - Wang, Lida; Deng, Ruijie; Li, Jinghong
Abstract : We report a DNA walking biosensor that can realize the detection of let-7a with a detection limit of 58 fM and high selectivity for resolving one nucleotide variation. Abstract : Artificial DNA motifs as architectural scaffolds have been widely used to assemble a variety of nanoscale devices. Synthetic DNA nanostructures have accomplished mechanical switching in response to external stimuli, suggesting the promise of constructing a walking device that is being used in the field of biosensors. Here, we design a novel miRNA-responsive DNA walker biosensor based on strand displacement cascades and an enzymatic recycling cleavage strategy. By using miRNA as a driving force, the DNA walkers can be activated to move along the track and generate specific signals for let-7a with a high signal-to-noise ratio. This biosensor exhibits excellent analytical performance toward the sensing of let-7a with great specificity for resolving one nucleotide variation and a detection limit of 58 fM. Such an ultraselective sensor shows that DNA nanostructures have great potential in providing platforms for applications in the fields of biosensing, clinical diagnostics and environmental sample analysis.